IMPLEMENTASI PEMBELAJARAN DASAR JARINGAN KOMPUTER PADA SISWA SISWI SD KARANGDADAP - Salwa Fitri Khaerunnisa; Hilyatul Fuadah; Rahma Nur Aulia; Luna Khairina; Ito Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study discusses the importance of understanding basic computer networks and the internet in the modern digital era where the world is increasingly connected. The rapid development of information and communication technology has made computer networks and the internet essential in supporting communication, education, business, and access to information. The objective of this research is to describe the concept of a connected world and explain the role of computer networks and the internet in everyday life. This research uses a descriptive method with a literature study approach. Data were collected from books, journals, and learning materials related to computer networks and internet usage. The results show that the internet provides significant benefits in various fields such as communication, education, entertainment, and business. However, the study also highlights negative impacts including addiction, the spread of hoaxes, and cyberbullying. The findings indicate that these impacts are closely related to how computer networks operate through hardware, software, transmission media, and data delivery mechanisms. The implication of this research emphasizes the importance of teaching computer network fundamentals and promoting responsible internet usage, especially for students, to maximize benefits and minimize risks in the digital environment.